2006
DOI: 10.1124/dmd.106.011692
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile of FYX-051 (4-(5-Pyridin-4-yl-1H-[1,2,4]triazol-3-yl)pyridine-2-carbonitrile) in the Rat, Dog, Monkey, and Human: Identification of N-Glucuronides and N-Glucosides

Abstract: ABSTRACT:FYX-051, 4-(5-pyridin-4-yl-1H-[1,2,4]triazol-3-yl)pyridine-2-carbonitrile, is a novel xanthine oxidoreductase inhibitor that can be used for the treatment of gout and hyperuricemia. We examined the metabolism of FYX-051 in rats, dogs, monkeys, and human volunteers after the p.o. administration of this inhibitor. The main metabolites in urine were pyridine N-oxide in rats, triazole Nglucoside in dogs, and triazole N-glucuronide in monkeys and humans, respectively. Furthermore, N-glucuronidation and N-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…NGlucosylation of xenobiotics in mammals has been observed for a limited number of drugs such as phenobarbital (Soine et al, 1994;Paibir et al, 2004), 4-(5-pyridin-4-yl-1H-[1,2,4]triazol-3-yl)pyridine-2-carbonitrile (FYX-051) (Nakazawa et al, 2006) and 5-aminosalicylic acid (Tjornelund et al, 1991), but to our knowledge, Nribosylation has not been reported previously. These ribose conjugates were detected only in feces and not observed in bile; therefore, it is likely the formation of these metabolites was due to gut microbial metabolism.…”
Section: Discussionmentioning
confidence: 90%
“…NGlucosylation of xenobiotics in mammals has been observed for a limited number of drugs such as phenobarbital (Soine et al, 1994;Paibir et al, 2004), 4-(5-pyridin-4-yl-1H-[1,2,4]triazol-3-yl)pyridine-2-carbonitrile (FYX-051) (Nakazawa et al, 2006) and 5-aminosalicylic acid (Tjornelund et al, 1991), but to our knowledge, Nribosylation has not been reported previously. These ribose conjugates were detected only in feces and not observed in bile; therefore, it is likely the formation of these metabolites was due to gut microbial metabolism.…”
Section: Discussionmentioning
confidence: 90%
“…Chemical shifts and coupling constants of tertiary N-glucuronides and ␤-anomers are found at 5.33 to 6.31 ppm and 8.3 to 9.5 Hz, respectively (Andersen et al, 1989;Keating et al, 2006;Nakazawa et al, 2006;Yan et al, 2006), which are at lower field (higher parts per million) than the anomeric proton of N-O-glucuronides (range of chemical shift 4.54 -4.84 ppm and coupling constants of 8.4 -9 Hz) (Straub et al, 1988;Delbressine et al, 1992;Turgeon et al, 1992;Schaber et al, 2001;and Miller et al, 2004). The N-Oglucuronide 3 fits the published range.…”
Section: Identification Of An N-oxide/n-glucuronide Metabolitementioning
confidence: 99%
“…The FYX-051 glucuronides were quantified by LC-MS/MS, according to a previously described method (Nakazawa et al, 2006) with a slight modification. A 5-l aliquot of the supernatant was injected into a LC-MS/MS unit consisting of a 1100 series high-performance liquid chromatography system (Agilent Technologies, Palo Alto, CA) and API 3000 (Applied Biosystems/MDS Sciex, Foster City, CA).…”
Section: Fyx-051 (mentioning
confidence: 99%
“…The metabolism of FYX-051 has been evaluated in rats, dogs, monkeys, and humans; its major metabolites in humans were identified as triazole N 1 -and N 2 -glucuronides, and they were excreted into urine at 43.3 and 16.1% of the dose, respectively, after the oral administration of FYX-051 (Nakazawa et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation